Praanggapan dalam Novel Nijushi no Hitomi Karya Sakae Tsuboi - Aryastini, Ni Made; Andry Anita Dewi, Ni Made; Anggraeny, Renny (Humanis, 2017)
This research dealt with “Presupposition in Nijushi no Hitomi by Sakae Tsuboi”. The aims of this research are to know the types of presupposition and the types of ilocutionary act that contain presupposition. This research uses the presupposition theory proposed by Yule (1996) and ilocutionary act theory proposed by Searle (1969). The results of this research showed that there were has six types of presupposition such as the existential, factive, lexical, structural, nonfactive, and counter factual presupposition. Meanwhile, the types of ilocutionary act that contain presupposition in Nijushi no Hitomi were assertives boasting, complaining, rejecting; directives commanding, inviting; expressives thanking, expressing sympathy, criticizing and declarations resigning.